Captain Awesome and the missing elephants - Kirby, Stan.; O'Connor, George (New York : Little Simon, 2014)
"On a class field trip to the Sunnyview Memorial Zoo, Eugene McGillicudy's favorite animals--the elephants--are missing! Is Randy the tour guide really the evil Raging Radonkey, trying to ruin the field trip? Can the Sunnyview Superhero Squad save the day and find the elephants?"--
NC640L
Keywords: Superheroes -- Fiction; School field trips -- Fiction; Lost and found possessions -- Fiction; Elephants -- Fiction; Zoos -- Fiction